Bibliometrics as a structuring tool in the production of knowledge in the area of ​​Regional Urban Planning and Demography - Lucas Filho, Antonio; Figueiredo, Fábio Fonseca; Barradas, Jaqueline Santos (Ciência da Informação em Revista, 2026)
With structures aimed at meeting the evaluation criteria adopted by the Coordination for the Improvement of Higher Education Personnel - CAPES, postgraduate programs, even if intrinsically, tend to develop considerable self-demand for incoming students, especially for those who They begin their journey in a large area of knowledge, inter and multidisciplinary, such as Urban and Regional Planning and Demography. In this way, the article sought to relate the theoretical-methodological aspects of the application of Bibliometrics in the development of all stages of research focused on the PLURD area. For this purpose, a bibliographic survey was carried out in order to describe the characteristics and aspects of the PLURD area and bibliometric analysis, as well as the mutuality of both based on the research stages defined by Villaça (2009). In this sense, it was possible to identify Bibliometrics as a tool for academic intellectual maturation, based on the process of quantifying the production of previous works, and in their appreciation, by identifying lines of analysis, methodologies, equipment, or even support, whether in corroboration of statements, or to rectify or validate data, facts, becoming a strategy to be adopted in improving the project. Therefore, the discipline’s dexterity stands out as a mechanism for planning and improving research stages, using its results as a source for the acquisition of knowledge, maturation and development of research, as well as for discussions and support of research results, even providing greater authenticity and credibility of the production.